Treatment of Trypanosoma cruzi infection in the undetermined phase. Experience and current guidelines of treatment in Argentina - Sosa-Estani, Sergio (1999)
Fil: Sosa Estani, Sergio. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación de Endemo-Epidemias; Argentina.